SPIRITUALITAS DALAM PERSPEKTIF TASAWUF DAN NEUROSAINS: RELASI KOMPLEMENTER ATAU KOMPARTEMEN? - Muhammad Naufal Waliyuddin (Refleksi: Jurnal Filsafat dan Pemikiran Keislaman, 2021)
Academic debates about spirituality have been going on for a long time with varied narratives. Sufism, as one who also discussed it, presents a view of spirituality in terms of Islamic metaphysics and meta-psychological understanding in the paradigm of interconnection between creation and the Creator. Meanwhile, Neuroscience, as a new science developed from the findings of Santiago Ramón y Cajal (1852-1934) regarding the nerve function of the human brain, presents a different view and tends to be rational, logical, and materialistic. This paper is a comparative study that discusses how the two sciences describe their explanations of spirituality. This literature research observes a number of relevant references, the latest research results, some debates in several forums, and then dissects it using critical discourse analysis. The results obtained indicate that there is a contradictory explanation on the one hand or a (separate) compartment between the meaning of spirituality in the Sufism perspective and the Neuroscience point of view. On the opposite side, there are several research efforts that elaborate spirituality in Sufism to have a complementary relationship (complementary) with Neuroscience. Even so, there is a kind of narrative impression that forces the concept of spirituality according to Neuroscience to support the conception of spirituality in the view of Sufism. As a follow-up discussion regarding this matter, it can be seen that there is a kind of research tendency that is testimonial and seeks confirmation of the initial assumptions of their research and builds arguments based on their tastes of knowledge.